Carboxylate functionalized waste wood-derived nanocellulose as carbon dot precursor for ferric ion sensing and multicolored bioimaging - Patel, Dinesh K.; Meenatchi, Venkatasamy; Won, So-Yeon; Han, Sung Soo (Cellulose (London), 2025)
Carbon dots (CDs) are considered attractive nanomaterials for bioimaging applications due to their remarkable physicochemical characteristics, including fluorescent properties, low toxicity, and good biocompatibility. However, an aggregation under the required media restricts the broad applicability of the CDs. To address this limitation, we developed carboxylate functionalized CDs from cellulose as a biocarbon precursor through the hydrothermal method. Nanocellulose was extracted from waste wood through chemical treatment. Ascorbic acid was utilized to functionalize the synthesized CDs. The prepared material was homogenously dispersed in different media, including water, ethanol, acetone, and dimethyl sulfoxide. It contained many polar functional groups, including carboxylic and hydroxy, causing a negatively charged surface. The CD solution exhibited an intense blue color on irradiating UV light (360 nm), showing fluorescence characteristics. Additionally, synthesized CDs demonstrated wavelength-dependent fluorescent properties with red shifting. The developed CDs showed superior sensitivity and selectivity for Fe 3+ , with a strong linear relationship between 0 and 2 µM and a detection limit of 15.08 µM. The synthesized CDs demonstrated > 96% recovery potential in actual samples. Furthermore, the synthesized CDs have no adverse effects on human dermal fibroblast cells, demonstrating their superior cytocompatibility. Cells were visualized with CDs under a fluorescence microscope at different excitation lights, showing their multicolored cellular imaging potential. Thus, the synthesized CDs have dual potential and can be explored as probes for sensing metal ions and cellular imaging. Graphical abstract